2021
DOI: 10.1136/bmjopen-2021-049093
|View full text |Cite
|
Sign up to set email alerts
|

Methods and results used in the development of a consensus-driven extension to the Consolidated Standards of Reporting Trials (CONSORT) statement for trials conducted using cohorts and routinely collected data (CONSORT-ROUTINE)

Abstract: ObjectivesRandomised controlled trials conducted using cohorts and routinely collected data, including registries, electronic health records and administrative databases, are increasingly used in healthcare intervention research. A Consolidated Standards of Reporting Trials (CONSORT) statement extension for trials conducted using cohorts and routinely collected data (CONSORT-ROUTINE) has been developed with the goal of improving reporting quality. This article describes the processes and methods used to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The extension was developed after a consensus driven process25 and included: confirmation of the need for a reporting guideline; a scoping review to assess reporting quality and identify reporting considerations to include in a preliminary checklist version26; a three round Delphi process to collect input on the checklist items from stakeholders, including reporting guideline developers, funders, journal editors, patient representatives, trial methodologists, epidemiologists, meta-research authors, ethicists, biostatisticians, and clinical trialists who were identified by members of the project team; a consensus meeting to advise on items to include and the checklist structure; and publication, dissemination, and implementation of the final checklist. Details on methods and results from each stage of the process are described elsewhere 27. In brief, 27 items for consideration were initially developed by members of the CONSORT Extension Project Team based on review of items included in the CONSORT 2010 statement,89 the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE)28 statement, and the REporting of studies Conducted using Observational Routinely collected Data (RECORD)29 statement, and also discussions with steering committee members.…”
Section: Development and Scope Of The Consort Extensionmentioning
confidence: 99%
“…The extension was developed after a consensus driven process25 and included: confirmation of the need for a reporting guideline; a scoping review to assess reporting quality and identify reporting considerations to include in a preliminary checklist version26; a three round Delphi process to collect input on the checklist items from stakeholders, including reporting guideline developers, funders, journal editors, patient representatives, trial methodologists, epidemiologists, meta-research authors, ethicists, biostatisticians, and clinical trialists who were identified by members of the project team; a consensus meeting to advise on items to include and the checklist structure; and publication, dissemination, and implementation of the final checklist. Details on methods and results from each stage of the process are described elsewhere 27. In brief, 27 items for consideration were initially developed by members of the CONSORT Extension Project Team based on review of items included in the CONSORT 2010 statement,89 the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE)28 statement, and the REporting of studies Conducted using Observational Routinely collected Data (RECORD)29 statement, and also discussions with steering committee members.…”
Section: Development and Scope Of The Consort Extensionmentioning
confidence: 99%
“…Our methodology will be guided by: the EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Network’s recommended steps for developing a health research reporting guideline, 34 and methodological considerations used to develop other recent or ongoing SPIRIT/CONSORT extensions (e.g., ACE (Adaptive designs CONSORT Extension), 35 CONSORT-ROUTINE 36 and dose-finding CONSORT extension 37 )…”
Section: Methodsmentioning
confidence: 99%
“…Secondary objectives will be to identify additional items not included in the initial list and allow for modifications in the wording of important items. 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 12 It offers a way for authors to organise reports of trial findings, facilitating their complete and transparent reporting, and aiding their critical analysis and interpretation. 13 An addition to the CONSORT statement was developed and it gives a list of essential elements that authors should include when describing the main outcomes of a randomised trial in a journal or conference abstract—CONSORT-A. 14 Those elements include recognising study as an RCT to allow indexing in databases, as well as description of the trials design, with contact details of a corresponding author to ask for additional information or clarification.…”
Section: Introductionmentioning
confidence: 99%